Роль комунікацій в формуванні креативного середовища для успішної реалізації проєктів в контексті «Perfomance Management» - Ровенська, В. В.; Смирнова, І. І.; Латишева, О. В.; Rovenska, V. V.; Latysheva, O. V.; Smyrnova, I. I. (Мукачівський державний університет, 2023)
У статті з’ясовано важливість та роль комунікацій в формуванні креативного середовища з метою успішної реалізації проєктів підвищення операційної ефективності на підприємстві. Досліджено світовий досвід командоутворення та гнучкого управління проєктами. Встановлено, що на формування ефективного та сприятливого креативного середовища значною мірою впливає вміння налагодити правильну комунікацію та здатність керівників використовувати весь можливий інструментарій налагодження колективної творчості. З’ясовані принципи ефективної комунікації. Розглянуто правила реалізації командної творчості. Наведено scrum- методологію прожект менеджменту щодо ролей керівників команди проєкту. Запропоновано схему управління конфліктами в команді для наочності результатів моніторингу ситуації в колективі і своєчасного виявлення як проблем в комунікації, так й результативності їх подолання.

For the successful development of the company and the improvement of operational efficiency in terms of digital transformation, leaders (project managers) who have new competencies are needed. The digital world, despite its "technicality", requires flexible skills – soft skills. These are communication skills, emotional intelligence, and creativity – competencies that allow you to offer innovative ideas, open a new perspective on familiar things. The article clarifies the importance and role of communications in the formation of a creative environment in order to successfully implement projects to improve operational efficiency at the enterprise. The global experience of team building and flexible project management was studied. It has been established that the formation of an effective and favorable creative environment is largely influenced by the ability to establish proper communication and the ability of managers to use all possible tools for establishing collective creativity. The principles of effective communication are clarified. The rules for the implementation of team creativity are considered. Scrum – project management methodology regarding the roles of project team leaders, which provides an opportunity for successful team building, proper communication in the project team, and timely resolution of conflicts, is presented. A scheme for managing conflicts in the team is proposed for visibility of the results of monitoring the situation in the team and timely identification of both communication problems and the effectiveness of their overcoming. It has been established that an ideal conflict-free state in creative collectives and creative organizations is almost impossible. Therefore, most efforts to completely eliminate conflicts turn out to be useless, and in addition, conflicts can have a positive effect. It is suggested that in order to create a favorable creative environment, ensure increased labor productivity and/or successful implementation of operational efficiency improvement projects, the team leader or project team manager at the enterprise should implement modern conflict management techniques. Managing conflicts, overcoming contradictions, eliminating the practice of "toxic" communication in creative teams for the successful generation of ideas is the key to the success of increasing operational efficiency at the enterprise.
The role of communications in shaping the creative environment for successful project implementation in the context of "Perfomance Management"
Keywords: комунікація; креативність; проєкт; операційна ефективність; команда; конфлікт; communication; creativity; project; operational efficiency; team; conflict